Discourses of criticality in Nordic countries’ school subject Civics - Ledman, Kristina (Umeå University, 2019)
Criticality (the ability to think, self-reflect and act critically, as well as reason analytically) is framed as an important goal of education generally, and citizenship education specifically. However, literature and research within subject didactics tend to frame criticality as subject-specific, hence its conceptualisation can vary substantially depending on epistemological and research traditions. Thus, this paper compares its treatment in the same subject, civics, in curricula of the five Nordic countries. Civics is an interesting case as it is a major element of citizenship education, which varies somewhat among the five countries. Four ideal types of criticality are elaborated and deployed in the analysis: general, disciplinary, moral and ideological criticality. The results reveal substantial differences between the five compared curricula. They also reveal apparent correlations between civics as a single-subject construct (as in Denmark and Sweden) and disciplinary criticality, and between civics as an integrated curriculum construct (as in Iceland) and general criticality. Overall, the disciplinary view of criticality slightly prevails in the five compared curricula. The results raise questions about contextual factors’ effects on how criticality is constructed in school subjects, and helps reflection on what we actually refer to when we talk about a certain school subject.